Tafsir Qaulan Sadidan dan Fenomena Hate speech: Relevansi Surah al-Aḥzāb: 70 dalam Etika Komunikasi Qur’ani - Muhammad Hilmi Arif Syauqi; Ahmad Nurrohim (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2026)
This study examines the meaning of qaulan sadīdan in Surah al-Aḥzāb: 70 and its relevance to hate speech within the framework of Qur’anic communication ethics. The study is motivated by the increasing spread of hate speech in digital spaces that damages social relations and human dignity. Using qualitative library research with a descriptive-comparative approach, this study analyzes the interpretations of qaulan sadīdan in three Indonesian tafsir works: Tafsir An-Nuur by Hasbi ash-Shiddieqy, Tafsir Al-Mishbah by M. Quraish Shihab, and Tafsir Al-Azhar by Hamka. The primary data are drawn from these three tafsir works, while secondary data are taken from scholarly literature on hate speech and Islamic communication ethics. The findings show that qaulan sadīdan refers not only to truthful speech, but also to precision, honesty, moral integrity, and constructive purpose. Therefore, Surah al-Aḥzāb: 70 remains relevant as a normative foundation for ethical, healthy, and responsible communication in contemporary digital society.